BIM related innovation in healthcare precinct design and facilities management - Thomson, Giles; Lindahl, Göran; Shemery, Ammar; Roupé, Mattias; Hampson, Keith D.; Johansson, Mikael (Emerald, 2019)
Purpose - The purpose of this paper is to introduce and discuss potential applications of emerging Building Information Model (BIM) and related technologies as applied to healthcare facilities. The paper presents example of applications of digital tools enabled by BIM that support more integrated outcomes for complex healthcare projects. Approach - Paper formulation by a transdisciplinary author group with ideas and approaches developed through discussions and writing to explore future research directions. Initial ideas are supplemented by a literature review with examples introduced where relevant. Findings - BIMas a front-end construction engineering tool is quite mature. Application of BIMand related tools to support complex healthcare at the precinct scale, for facilities management (FM), including improved user experience (UX) has been limited but shows great promise to support complex healthcare projects. Research Limitations/Implications - The research presented is limited and exploratory as it represents the first step by this group to investigate an integrated approach to digital healthcare design and FM. Practical Implications - The paper introduces the considerable benefits of BIM models, and related tools for FM and/or UX (both staff and patients) to save time, money and improves efficiency and accuracy in healthcare facilities. Originality/Value - The transdisciplinary author group brought broad perspectives to the potential benefits of combining accurate data-rich legacy building models with other digital tools for increased integration and co-ordination at all life stages of a healthcare precinct.